Effects of Induced Moisture Loss in Chicken Embryos at Embryonic Day 18 and Post-hatch Immune Response During Salmonella enteritidis Lipopolysaccharide Challenge in Broilers - Gregorich, Jenna L.; Lilburn, Michael S.; Shanmugasundaram, Revathi (Frontiers in Physiology, 2022)
Two experiments were conducted to investigate the effects of induced moisture loss on embryonic development and the immune response following an inflammatory challenge. In Experiment I, fertile leghorn eggs (n=100) and commercial broiler eggs (n=300) were set at 37.5°C and moisture loss was induced in one-half of the Leghorn and broiler eggs by drilling two, 1.5 mm diameter holes. The Control eggs had 0 holes. At embryonic day (ED)18, layer and broiler eggs in the 2-hole treatment had a significant (P < 0.01) increase in moisture loss compared to the control treatment (10.1% vs. 8.2%; 9.9% vs. 8.4%). Thymocytes from leghorn (104%) and broiler (62%) embryos in the 2-holes treatment had significantly increased in vitro proliferation compared with the control embryos (P < 0.05). At ED18, layer and broiler embryos in the 2-hole treatment had an approximate 2 fold increase in the splenic CD8+/CD4+ ratio (P < 0.05) and CD4+CD25+ cells percentage in both the thymus and spleen (P < 0.05). At ED18, both layer and broiler embryos from the 2-hole treatment had a significant increase in splenic IL1-β, IL-6, IL-10, and TLR-4 mRNA transcription compared to the control group (P < 0.05). Experiment II was repeated with 300 fertile broiler eggs. Chicks were randomly distributed into one of four treatments in a 2 (0, 2 holes) X 2 (0, 500 µg LPS) factorial setup. At 24h and 48h post-hatch, chicks hatched from eggs with 2-holes and challenged with LPS had a significant increase (P < 0.05) in thymocyte proliferation at 24h and 48h when compared with chicks hatched from the control (0-hole; 0 µg LPS) treatment. Chicks hatched from the 2- hole treatment and challenged with the LPS had an approximately 2 fold higher splenic CD8+/CD4+ ratio and 1.5 fold increase in CD4+CD25+ percentage compared to control chicks (P ≤ 0.05). In chicks hatched from the 2-hole treatment, MUC2 mRNA transcription was comparable to control chicks at 24h and 48h in response to the LPS challenge. Our data suggest that the 2-hole treatment reprograms gene transcription to facilitate cell survival via proliferation and differentiation during an LPS inflammatory challenge.